PELAKSANAAN TUGAS STEWARD DI HOTEL GRAND CENTRAL PEKANBARU - Siti Natasha; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Tourism is mega business, not only as a needed but also as a want. In the world of tourism industry, one of the most important is accommodation, therefore in Pekanbaru the Grand Central Hotel is one of hotels that frequently visited. Not only selling rooms this hotel also selling food and beverage service like restaurant, bar, room service. Guest who is visit here are not just for stay overnight, many of them also just visit restaurant, bar or meeting at rooms available at hotel or use ballroom and make celebrate party as birthday or wedding. Therefore with this research the writer wants to describe food and beverage service with main discussion of providing and maintaining equipment for food and beverage department. Through pre-observation it is known that providing and maintaining equipment for service and product is steward in organization under food and beverage department. Continued with observations, interviews and documentation with HRD and Food and Beverage Department especially supervisor steward, and steward. Also writer get some information or data source such as social media and flyers by Grand Central Hotel Pekanbaru. Keywords: Steward, providing and maintaining equipment.